Analyzing Global Industry Dynamics Using Porter’s Five Forces And Ratio Analysis Model - Waworuntu, Evi Christy; Yasuwito, Merry; Sumanti, Elvis (SEAN Institute, 2024)
The importance of financial strategy in facing the ever-changing dynamics of the global market. Referring to Porter's Five Forces concept, this research highlights its influence on industry profitability and a company's ability to compete. The analysis reveals how external factors, such as globalization and technological transformation, impact the strategies and competitive positions of companies in specific industries. Accompanied by case studies, the research emphasizes the interconnectedness between financial analysis and the external environmental dynamics viewed through the lens of Porter's Five Forces. The objective is to identify changes in a company's financial strategy in response to shifts in the business environment and uncover the interactions between Porter's Five Forces factors and financial performance, both at regional and global levels. The study results underscore that the global industry presents high barriers for new entrants due to economies of scale and significant investments made by established companies. Financial ratio analysis also depicts the liquidity, solvency, and profitability of these companies, showcasing varying trends from one company to another. Factors influencing the global industry, such as high entry barriers, strong bargaining power of buyers, and the threat of substitute products, directly impact the financial conditions and profitability of companies. The ability of companies to manage risks and their financial strategies plays a key role in responding to challenges and opportunities in the dynamic business environment.